Alliances between the Mongols and the Franks Against Mamluk Naval State (Damascus University Journal of arts and humanities sciences, 2021)
This research deals with the alliances between the Mongols and the Franks against Egypt and the Levant, which was controlled by the Mamluk state in the 7th and 8th/AD 13th/AD 14th centuries. During the rule of four dynasties of the Mamluk sultans: Al-Zaher Baybars, Al-Mansur Qalawun, Nasser Mohammed bin Qalawun. These alliances have shown the common objectives of the Mongols and the Franks, and their striving to achieve them. These alliances were characterized by seriousness and continuity, including most of the Mamluk naval rule.
Keywords: Alliances between the Mongols and the Franks Against Mamluk Naval State